Modal analysis of a centrifugal pump impeller using finite element method - Ashri, M. (EDP Sciences, 2014)
The turbo machinery design has evolved rapidly in the last 50 years. The development in the design of any turbo machinery involves interdisciplinary process, namely stress analysis, vibration analysis, fluid dynamics, thermodynamics and the material selection. One of the major and common analyses used in the development of any mechanical part subjected to dynamic loading is the modal analysis. In this paper, the dynamic characteristics of an impeller of a centrifugal pump were studied. The dynamics characteristics studied were limited to the natural frequencies and the mode shapes. The impeller chosen for the study was a single-entry impeller with radial vanes. Finite element method (FEM) was used since it has proven to be an alternative approach to the experimental method for the vibrational behavior analysis of a component or a system. Modeling and simulation of the impeller have been carried out using ANSYS Bladegen and ANSYS Workbench software, respectively. The eigenvalues and the eigenvectors were observed, and they represent the frequencies and the corresponding mode shapes of the impeller, respectively. The results showed that the varying number of impeller blades and impeller blade thickness had minimal effect on frequencies. However, the change to the impeller disk thickness had significant effects on the natural frequency of the impeller. Â© 2014 Owned by the authors, published by EDP Sciences.